Excessive exposure of sick neonates to sound during transport. Issue 6 (1st November 2003) - Buckland, L; Austin, N; Jackson, A; Inder, T
Abstract : Objective: To determine the levels of sound to which infants are exposed during routine transport by ambulance, aircraft, and helicopter. Design: Sound levels during 38 consecutive journeys from a regional level III neonatal intensive care unit were recorded using a calibrated data logging sound meter (Quest 2900). The meter was set to record "A" weighted slow response integrated sound levels, which emulates the response of the human ear, and "C" weighted response sound levels as a measure of total sound level exposure for all frequencies. The information was downloaded to a computer using MS HyperTerminal. The resulting data were stored, and a graphical profile was generated for each journey using SigmaPlot software. Setting: Eight journeys involved ambulance transport on country roads, 24 involved fixed wing aircraft, and four were by helicopter. Main outcome measures: Relations between decibel levels and events or changes in transport mode were established by correlating the time logged on the sound meter with the standard transport documentation sheet. Results: The highest sound levels were recorded during air transport. However, mean sound levels for all modes of transport exceeded the recommended levels for neonatal intensive care. The maximum sound levels recorded were extremely high at greater than 80 dB in the "A" weighted hearing range and greater than 120 dB in the total frequency range. Conclusions: This study raises major concerns about the excessive exposure of the sick newborn to sound during transportation.